Current direction and advances in analytical sample extraction techniques for drugs with special emphasis on bioanalysis. (21st January 2019) - Navitha Reddy, Gangireddy; Dilip Zagade, Aarati; Sengupta, Pinaki
Analytical techniques may not be compatible or sufficiently sensitive to the analytes, unless it undergoes a specific sample extraction procedure. Sample extraction can be considered as one of the key steps in analysis. Analysis of a poorly treated sample may produce inferior quality of analytical data. Continuous advancement and development of newer sample extraction techniques such as solid phase microextraction, ultrasound, magnetically and microwave assisted magnetic extraction; electro-membrane extraction and dried blood spotting are to address the shortcomings of the existing techniques and to provide more automation, minimizing preparation time and make them high throughput. This review summarizes the suitability of application of the advanced sample preparation techniques available for chemical and bioanalysis in a comprehensive manner. This review also provides a scientific guidance for selecting the appropriate sample extraction technique based on sample type.